2022
DOI: 10.1038/s41598-022-18969-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a scoring system for assessing incisions in laser surgery

Abstract: The idea of laser surgery is nearly as old as the laser itself. From the first trials to modern laser surgery systems, it was and is the aim to selectively cut the tissue in the focus spot without causing harm to surrounding structures. This is only possible when the correct parameters for the surgical laser are chosen. Usually, this is done by parameter studies. However, the concrete evaluation scheme often differs between groups and more precise approaches require staining and microscopic evaluation. To over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Experiment A For the quantitative analysis all cuts scored on the scoring system presented in a previous paper 30 from our group (especially Fig. 2 provides an good overview).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Experiment A For the quantitative analysis all cuts scored on the scoring system presented in a previous paper 30 from our group (especially Fig. 2 provides an good overview).…”
Section: Discussionmentioning
confidence: 99%
“…The cut shown there would be scored as 2. As it could be shown that the scoring of the cutting front is more reliable 30 , the complete analysis in the study is based on the scores of the cutting front.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations